Analisis Faktor Keterlambatan COD Proyek PLN UIP Kalbagtim dengan Metode Analytical Hierarchy Process dan Fault Tree Analysis - Avira Dinda Pradiani; Nunung Nurhasanah (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
PLN Unit Induk Pembangunan Kalimantan Bagian Timur (PLN UIP Kalbagtim) is a company that is responsible for electricity needs in the East Kalimantan region. PLN UIP Kalbagtim covers three types of projects. There are power projects, substation projects, and transmission projects. However, many of these projects experienced delays in their Commercial Operation Date (COD). PLN UIP Kalbagtim only measures the risk level generally and does not measure the root causes of the possible occurrence of this risk. Based on these problems, a study was conducted to identify the projects that experienced delays the most using the Pareto diagram, then analyzed the factors and root causes of the delay using a fish-bone diagram, then using the Analytical Hierarchy Process method, data processing was done to obtain the probability value of each root event. Furthermore, using the Fault Tree Analysis method, the probability value of delay is calculated until the smallest value is found. From the research that has been done, it can be concluded that the transmission project in the form of SUTT is the project that most often experiences delays due to machine, man, material, method, and money factors. The factor that must be set as the priority or focus of the company is the money factor and the root of the incident in it will also be automatically deleted so that the possibility of delays is reduced from 52.71% to 25.28%. Keywords - Analytical Hierarchy Process, Fault Tree Analysis, Pareto Chart, Fish-bone Diagram